Mega Projects and the Enhancement of Saudi Arabia’s Soft Power An Analytical Study of the Media Content of Selected Accounts of Vision 2030 Mega Projects on the (X) Platform - Al-Yahya, Hadeel Ali (Journal of Posthumanism, 2025)
This study aims to identify the extent to which the administrators of the mega projects stemming from Saudi Vision 2030 employ media content in enhancing the soft power of the Kingdom of Saudi Arabia. This is pursued through analyzing the official accounts of these projects on the (X) platform, in order to determine the most prominent themes they present, the objectives they emphasize, as well as monitoring the communication strategies employed in these accounts and the level of audience engagement with the produced content. The study further seeks to outline the features of soft power generated through these accounts.The study belongs to the category of descriptive survey studies, relying on content analysis as the primary tool to examine the media content published through the accounts of Vision 2030 mega projects on the (X) platform. The sample was limited to the official accounts of NEOM, the Red Sea Global (RSG), Qiddiya, and Diriyah Gate Development Authority.The most significant findings of the study revealed that the main themes addressed in these accounts centered on Saudi national occasions, the promotion of the projects themselves, and tourism, in addition to economic, social, and environmental topics. The four accounts (the sample) devoted considerable attention to the different types of influence. However, the Red Sea Global (RSG) distinctly emphasized cognitive influence, while the Diriyah Gate Development Authority adopted a balance between cognitive, affective, and behavioral influence, with a stronger tendency toward cognitive persuasion. Qiddiya sought to enhance behavioral influence, whereas the NEOM account presented a combination of cognitive and emotional appeals reinforced with behavioral elements.The study also revealed that the four accounts employed various communication strategies, with patterns of usage differing from one account to another, and that the strategy of media dissemination received the highest level of attention. Furthermore, the results demonstrated a clear diversity in addressing target audiences across the four accounts (the sample), with statistically significant differences among them. This indicates variations in the targeting and communication strategies adopted by each account.